Analysis of Students’ Problems in Determining Adjective Clause of Report Text at Grade XI of SMAN 2 Kerinci Academic Years 2015/2016 - Efa Silfia; Novi Riany (Jurnal Ilmiah Dikdaya, 2021)
One of them carries out important rule that is using adjective clauses especially who, which, when, and where. Based on the finding above, it can be seen that students who has understood what adjevtive clause is and how to find out in the report text. This research was aimed to find out students’ problems in determining adjective clause of report text at grade XI of SMAN 2 Kerinci Academic Years 2015/2016. And to find out the causes of students’ problems in determining adjective clause of report text at grade XI of SMAN 2 Kerinci Academic Years 2015/2016. The method of this research was descriptive reserach. The sample of this research was class XI IA1 of SMAN 2 Kerinci. There were 28 students. The data were collected by using grammar test for quantitative data and using interview for qualitative data. The result of this research showed that the students at XI IA1 of SMAN 2 Kerinci were very good in determining adjective clause of report text. It indicated the mean of students’ score. It was 71.5 The researcher found that most of the students were able to determine adjective clauses of report text and few of them didn’t understand how to use them. It can be concluded that the students problems in determining adjective clauses of report text were no gotten by all students. It was concluded that the students’ problems in determining adjective clauses of report text was good. It is caused the students did not understand what their teacher had taught about tenses especially adjective clauses, they felt bored to study grammar.